A low-absorption high-reflectivity multilayer composite thermal control coating

By introducing a multilayer composite structure of CsZnBr3 chiral perovskite polarizing material and silicon-oxygen prepolymer binder into the inorganic thermal control coating, the shortcomings of the inorganic thermal control coating in terms of solar absorptivity and reflectivity are solved, and the reflectivity and stability of the coating are improved, making it suitable for the complex environment of spacecraft.

CN121160219BActive Publication Date: 2026-07-07BEIJING MICROENTHALPY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511512700.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2026-07-07
Estimated Expiration
2045-10-22

AI Technical Summary

Technical Problem

Existing inorganic thermal control coatings have room for improvement in terms of solar absorptivity and reflectivity. Furthermore, single coatings have limited functionality, and composite coatings are difficult to apply and lack stability.

Method used

A multi-layer composite structure consisting of ZnO coating and inorganic polarizing material coating is adopted. The polarization properties of CsZnBr3 chiral perovskite and the silicon-oxygen prepolymer binder are utilized to form a multi-layer composite thermal control coating through a spraying process, which improves reflectivity and reduces solar absorptivity.

Benefits of technology

It improves solar reflectivity, reduces solar absorptivity, and enhances the structural stability of the coating, making it suitable for the complex environment of spacecraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121160219B_ABST
    Figure CN121160219B_ABST
Patent Text Reader

Abstract

The application provides a multilayer composite thermal control coating, which comprises a ZnO coating and an inorganic polarizing material coating, and utilizes scattering and polarization of the inorganic polarizing material to improve solar tube reflectivity of the composite thermal control coating and reduce a solar light absorption ratio; the inorganic polarizing material is a CsZnBr3 chiral perovskite, and a silicon-oxygen prepolymer is used as a binder, and the inorganic polarizing material has high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the aerospace field, specifically relating to a high-reflectivity multilayer composite thermal control coating. Background Technology

[0002] Thermal control coatings regulate the temperature of spacecraft surfaces through their own thermophysical properties, namely solar absorptivity (αs) and emissivity (εH). Low-ratio paint-type inorganic thermal control coatings exhibit excellent stability in the space environment, making them the preferred thermal control material for large-area heat dissipation surfaces of high-performance spacecraft radiators. Paint-type inorganic thermal control coatings typically consist of two parts: pigments and inorganic binders. By using pigments with different thermal radiation properties and different types of binders, a series of thermal control coatings with different ratios can be obtained (such as low solar absorptivity inorganic white paint and high solar absorptivity inorganic black paint), which are important thermal control materials for passive thermal control systems.

[0003] For a long time, both domestic and international researchers have been developing inorganic thermal control coatings with low solar absorptivity and high stability, mainly including: ① modification of traditional pigments; ② development of new material systems for pigments. Traditional pigments mainly include ZnO, TiO2, Zn2TiO4, SiO2, Al powder, etc. In 1991, the IITRI Research Institute in the United States developed a white paint coating of type YB-71, using zinc titanate as pigment and K2SiO3 as binder. It has strong resistance to atomic oxygen attack, but is easily contaminated and expensive. In 1993, the IITRI Research Institute in the United States manufactured a white paint of type S13G / LO-1, using ZnO coated with K2SiO3 as pigment and polymethylsiloxane as binder. It is the fourth generation of white paint coatings in the S-13 series. Its application is much easier than that of the YB-71 coating. However, gas evolution occurs in a vacuum environment, and the contamination problem is similar. In June 2023, Chen Junke, Yu Yang, and others from the Shanghai Institute of Ceramics, Chinese Academy of Sciences, and the Center for Materials and Optoelectronics, University of Chinese Academy of Sciences, developed a core-shell structured pigment, Zn2SiO4@SiO2, which has a low solar absorptivity and high emissivity, and stronger heat dissipation capabilities. Compared with Zn2SiO4 pigment, the shell SiO2 structure can act as a buffer layer, reducing the interaction between the space irradiation source and the core pigment, and significantly improving ultraviolet irradiation stability.

[0004] The functionality of a single coating is relatively limited, and some literature employs multi-layer composite structures to enrich the functionality of thermal control coatings. CN101152777A discloses a method for improving the performance of variable emissivity thermal control coatings by depositing multi-layer infrared films on the upper or lower surfaces of the phase change layer in the thermal control coating. CN102176102A discloses a variable emissivity and variable reflectivity electrochromic smart thermal control coating, comprising a substrate layer, an electrode layer, an electrolyte layer, a porous support layer, an electrochromic active layer, and an environmental encapsulation layer.

[0005] Inorganic thermal control coatings have limitations such as high curing temperature and high surface brittleness. Composite coatings need to take into account the difficulty of the coating process. In addition, there is still room for improvement in terms of solar absorptivity and reflectivity. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a multilayer composite thermal control coating comprising a ZnO coating and an inorganic polarizing material coating. By utilizing the scattering and polarization properties of the inorganic polarizing material, the reflectivity of the solar tube in the composite thermal control coating is improved, and the solar absorption ratio is reduced.

[0007] The present invention adopts the following technical solution:

[0008] A multilayer composite thermal control coating comprises a ZnO coating and an inorganic polarizing material coating, wherein the inorganic polarizing material is a chiral perovskite with the general structural formula CsZnBr3, and is prepared by the following method:

[0009] (1) Preparation of CsZnBr3 chiral perovskite, the preparation steps include preparing CsZnBr3 nanocrystals, mixing with chiral organic ammonium halide salt solution, centrifugation and washing to obtain CsZnBr3 chiral perovskite;

[0010] (2) Tetraethyl orthosilicate is mixed with water or an aqueous catalyst solution and hydrolyzed and condensed to form a prepolymer binder;

[0011] (3) The prepolymer binder and silane coupling agent are mixed with ZnO pigment and CsZnBr3 chiral perovskite respectively to obtain the raw materials for ZnO coating and inorganic polarization material coating. The multilayer ZnO coating and inorganic polarization material coating are sprayed onto the substrate by spraying process to obtain the multilayer composite thermal control coating.

[0012] In some embodiments, the CsZnBr3 chiral perovskite can be prepared using existing techniques, employing a one-pot method with ZnBr2 and CsBr to prepare CsZnBr3 nanocrystals, which are then combined with chiral organic ammonium halide salts to form a chiral perovskite. In one specific embodiment, step (1) of preparing the CsZnBr3 chiral perovskite includes the following steps:

[0013] (1-1) Add 0.5~2 mol ZnBr2 and 0.5~2 mol CsBr to 50 mL of anhydrous DMF, mix them, and then add oleylamine and oleic acid in a volume ratio of 1:5~10, with a total volume of 10~20 mL.

[0014] (1-2) Stir at room temperature for 20-60 min, then add 50-100 mL of a 1:1 mixture of acetone and isopropanol to separate and obtain CsZnBr3 nanocrystals;

[0015] (1-3) CsZnBr3 nanocrystals were dispersed in 100 mL of methyl acetate solution, and then mixed with 100 mL of 10~30 wt% S(R)-BABr methyl acetate solution. The mixture was stirred for 10~60 min, centrifuged and washed to obtain CsZnBr3 chiral perovskite.

[0016] In some implementations, in step (2), the catalyst is 0.01~0.1 mol / L hydrochloric acid, sulfuric acid, sodium hydroxide, potassium hydroxide or sodium carbonate; the mass ratio of tetraethyl orthosilicate to water or aqueous catalyst solution is 1:0.05~0.2, and hydrolysis and polycondensation are carried out for a certain period of time until a sol-gel is formed, and the mixture can also be heated and refluxed; depending on the amount and the catalyst, the hydrolysis and polycondensation time can be 0.5~10h.

[0017] In some embodiments, in step (3), the silane coupling agent is selected from γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane.

[0018] In some implementations, the mass ratio of prepolymer binder, silane coupling agent, and ZnO pigment in step (3) is 10~30:1~2:60~90; the mass ratio of prepolymer binder, silane coupling agent, and CsZnBr3 chiral perovskite is 50~70:1~2:30~50. After mixing, it can be further mixed thoroughly by ball milling.

[0019] In some embodiments, the multilayer composite thermal control coating comprises 10-15 layers, including 3-5 layers of inorganic polarizing material coating, each layer with a thickness of 5-10 μm. Using N2 as the spray carrier gas, the liquid material is sprayed onto substrates such as aluminum substrates and fiberglass. The spraying method may involve spraying 2-3 layers of ZnO coating, spraying 1 layer of inorganic polarizing material coating, then spraying 1-2 more layers of ZnO coating, and so on. A time interval, such as 3 hours, is allowed between multiple spray layers to allow the coating surface to dry before spraying the next layer.

[0020] Compared with the prior art, the beneficial effects of the present invention include at least the following:

[0021] 1. This invention synthesizes CsZnBr3 chiral perovskite, which has circular polarization. Since the polarization direction of sunlight is random, CsZnBr3 chiral perovskite can block part of the sunlight and improve reflectivity. It is prepared into an inorganic polarization coating and combined with a ZnO coating to form a multilayer composite thermal control coating. Compared with a simple ZnO coating, it has improved reflectivity and reduced the absorption ratio of sunlight.

[0022] 2. The present invention uses silicon-oxygen prepolymer as a binder to prepare a multilayer composite thermal control coating that is free of organic matter, has high structural stability, and is suitable for the complex operating environment of spacecraft. Attached Figure Description

[0023] Figure 1 The CPL spectrum of the CsZnBr3 chiral perovskite prepared in Example 1 is shown.

[0024] Figure 2 This is a schematic diagram of the structure of the multilayer thermal control coating in Example 2. Detailed Implementation

[0025] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Examples of the embodiments are shown in the accompanying drawings. It should be understood that the specific embodiments described in the following embodiments of the invention are merely illustrative examples of specific implementations of the invention and are intended to explain the invention, but do not constitute a limitation thereof.

[0026] The endpoints of the ranges and any values ​​disclosed herein are not limited to the exact ranges or values, which should be understood to include those close to them.

[0027] Example 1: Preparation of CsZnBr3 chiral perovskite

[0028] The preparation of CsZnBr3 chiral perovskite includes the following steps:

[0029] 1. Add 1 mol ZnBr2 and 1 mol CsBr to 50 mL of anhydrous DMF and heat to dissolve. Mix the two solutions thoroughly, then add 2 mL of a mixed solution of oleylamine and 4 mL of oleic acid.

[0030] 2. Stir slowly at room temperature for 20-60 minutes to carry out the reaction, then add 100 mL of a 1:1 mixture of acetone and isopropanol, and obtain CsZnBr3 nanocrystals by centrifugation.

[0031] 3. CsZnBr3 nanocrystals were then dispersed in 100 mL of methyl acetate solution and mixed with 100 mL of 20 wt% S(R)-BABr methyl acetate solution. The mixture was stirred for 30 min, and the precipitate was separated by centrifugation. The precipitate was washed with methyl acetate and deionized water in sequence and dried to obtain CsZnBr3 chiral perovskite.

[0032] The circular polarization (S(R)-BABr) of CsZnBr3 chiral perovskite was determined, and its CPL spectrum is shown below. Figure 1 As shown, it can be seen that CsZnBr3 chiral perovskite has circular polarization.

[0033] Example 2: Preparation of multilayer thermal control coating

[0034] 1. Adhesive preparation: Tetraethyl orthosilicate and water are mixed at a mass ratio of 10:1 and heated under reflux at 80°C for 3 hours to hydrolyze and condense to form a prepolymer adhesive;

[0035] 2. Add γ-aminopropyltriethoxysilane and ZnO pigment to the prepolymer binder in a mass ratio of 24:1:75, and ball mill for 12 hours to obtain the raw material for the ZnO coating; add γ-aminopropyltriethoxysilane and CsZnBr3 chiral perovskite (S-BABr) to the prepolymer binder in a mass ratio of 49:1:40, stir and ultrasonically vibrate to mix evenly to obtain the raw material for the inorganic polarization material coating.

[0036] 3. The raw materials for both coatings were screen-filtered into slurries and sprayed for later use. Using N2 as the carrier gas, the coating materials were sprayed onto the aluminum substrate. First, three layers of ZnO coating were sprayed, each approximately 7 μm thick. The coating thickness was measured in real-time using an OU3500 coating thickness measuring instrument. Then, three coats were applied, alternating between one layer of inorganic polarizing material coating and two layers of ZnO coating. After each coating layer was sprayed, it was dried for 3 hours. Preliminary assessment indicated that the internal condensation reaction within the coating was essentially complete before continuing with the next layer. This resulted in the multilayer thermal control coating for the experimental group, as shown in the schematic diagram below. Figure 2 As shown. In addition, a control group was prepared by spraying 12 layers of ZnO coating using a similar method.

[0037] Performance tests were conducted on the experimental and control groups to evaluate the technical effectiveness of the composite coating.

[0038] (1) Solar reflectance

[0039] The substrate and coating were divided into three parts, and their reflectance was measured separately. A LAMBDA 950 UV / VIS / NIR spectrophotometer (Perkin Elmer) was used to measure the solar reflectance of the experimental and control group coatings. The results are shown in Table 1. The reflectance of the experimental group was greater than that of the control group, with a more significant increase in reflectance in the ultraviolet region. This is mainly because ZnO absorbs ultraviolet light, reducing reflectance, while the polarizing material reduces ultraviolet absorption.

[0040]

[0041] (2) Adhesion test

[0042] According to the requirements of GJB2704A-2006, adhesive tape with a peel strength of 2N / cm-4N / cm was applied tightly to the middle area of ​​the coating, at least 3mm away from the edge. One end of the tape was pulled up by hand, making a 90° angle between the tape and the surface. After slowly (about 5mm / s) pulling the tape away from the surface, the adhesion rating of both the experimental group and the control group was 0.

[0043] (3) Thermal stability

[0044] Using a thermal shock test chamber (TSD-101-W), the coatings of both the experimental and control groups were subjected to 100 thermal cycles from -100℃ to +100℃ under normal atmospheric conditions. The appearance was then observed and the solar reflectance was measured. The results showed that both the experimental and control groups maintained intact appearance and good adhesion, with essentially unchanged solar reflectance; this indicates that the adhesive and all-inorganic coating raw materials used in this invention possess high thermal stability.

[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and do not constitute a limitation on the content of the present invention. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including combining various technical features in any other suitable manner. These simple modifications and combinations should also be regarded as the content disclosed in the present invention and all fall within the protection scope of the present invention.

Claims

1. A multilayer composite thermal control coating, characterized in that, The coating includes a ZnO coating and an inorganic polarizing material coating. The inorganic polarizing material is a chiral perovskite with the general structural formula CsZnBr3, and is prepared using the following method: (1) Preparation of CsZnBr3 chiral perovskite, the preparation steps include preparing CsZnBr3 nanocrystals, mixing with chiral organic ammonium halide salt solution, centrifugation and washing to obtain CsZnBr3 chiral perovskite; (2) Tetraethyl orthosilicate is mixed with water or an aqueous catalyst solution and hydrolyzed and condensed to form a prepolymer binder; (3) The prepolymer binder and silane coupling agent are mixed with ZnO pigment and CsZnBr3 chiral perovskite respectively to obtain the raw materials for ZnO coating and inorganic polarization material coating. The multilayer ZnO coating and inorganic polarization material coating are sprayed onto the substrate by spraying process to obtain the multilayer composite thermal control coating. In step (1), the preparation of CsZnBr3 chiral perovskite includes the following steps: (1-1) Add 0.5~2 mol ZnBr2 and 0.5~2 mol CsBr to 50 mL of anhydrous DMF, mix them, and then add oleylamine and oleic acid in a volume ratio of 1:5~10, with a total volume of 10~20 mL. (1-2) Stir at room temperature for 20-60 min, then add 50-100 mL of a 1:1 mixture of acetone and isopropanol to separate and obtain CsZnBr3 nanocrystals; (1-3) Disperse CsZnBr3 nanocrystals in 100 mL of methyl acetate solution, then mix with 100 mL of 10~30 wt% S-BABr or R-BABr methyl acetate solution, stir continuously for 10~60 min, centrifuge and wash to obtain CsZnBr3 chiral perovskite.

2. The multilayer composite thermal control coating as described in claim 1, characterized in that, In step (2), the catalyst is 0.01~0.1 mol / L of hydrochloric acid, sulfuric acid, sodium hydroxide, potassium hydroxide or sodium carbonate.

3. The multilayer composite thermal control coating as described in claim 1, characterized in that, In step (2), the mass ratio of tetraethyl orthosilicate to water or aqueous catalyst solution is 1:0.05~0.2, and the hydrolysis and polycondensation time is 0.5~10h.

4. The multilayer composite thermal control coating as described in claim 1, characterized in that, In step (3), the silane coupling agent is selected from γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane.

5. The multilayer composite thermal control coating as described in claim 1, characterized in that, In step (3), the mass ratio of prepolymer binder, silane coupling agent and ZnO pigment is 10~30:1~2:60~90.

6. The multilayer composite thermal control coating as described in claim 1, characterized in that, The mass ratio of prepolymer binder, silane coupling agent and CsZnBr3 chiral perovskite is 50~70:1~2:30~50.

7. The multilayer composite thermal control coating as described in claim 1, characterized in that, The multilayer composite thermal control coating consists of 10 to 15 layers, including 3 to 5 layers of inorganic polarizing material coating, with each layer having a thickness of 5 to 10 μm.

Citation Information

Patent Citations

  • Method for improving variable emissivity heat-controlled coating capability

    CN101152777A

  • Variable emissivity and variable reflectivity electrochromic intelligent thermal control coating and preparation method

    CN102176102A

  • Chiral perovskite nanowire with circular polarization luminescence characteristic and preparation method thereof

    CN116063185A